The Other Side of the Coin The Comparative Evidence of Cash and in-Kind Transfers in Humanitarian Situations? - Gentilini, Ugo (The World Bank, 2016)
In other words, the appropriateness of transfers cannot be predetermined and should emerge from response analysis that considers program objectives, the level of market functionality, predicted cost-effectiveness, implementation capacity, the management of key risks such as on protection and gender, political economy, beneficiary preferences, and resource availability. Finally, it seems possible (and necessary) to reconcile humanitarian imperatives with solid research to inform decision-making, especially on dimensions beyond food security